2021
DOI: 10.1186/s12970-021-00449-x
|View full text |Cite
|
Sign up to set email alerts
|

Broad Spectrum Polyphenol Supplementation from Tart Cherry Extract on Markers of Recovery from Intense Resistance Exercise

Abstract: Background Tart cherry supplementation has been shown to enhance recovery from strenuous exercise due to its antioxidant properties. The majority of these studies used tart cherry juice, with a significant calorie content. The primary purpose of this study was to assess whether powdered tart cherry extract with minimal calorie content reduces oxidative stress and enhances recovery following intense resistance exercise. Methods Thirteen men (mean ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…The values for handgrip strength observed in this study were comparable to normative values of the UK biobank, as well as a cohort from the United States within the same age group (33,34). Only two previous studies have investigated the effects of a polyphenol-rich intervention on handgrip strength, both of which were performed in male adults (35,36). Supplementation with grape juice in male volleyball athletes did not result in improved handgrip strength (35), while a significant improvement in handgrip strength 24 hours after intense resistance exercise was observed in male adults (36).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The values for handgrip strength observed in this study were comparable to normative values of the UK biobank, as well as a cohort from the United States within the same age group (33,34). Only two previous studies have investigated the effects of a polyphenol-rich intervention on handgrip strength, both of which were performed in male adults (35,36). Supplementation with grape juice in male volleyball athletes did not result in improved handgrip strength (35), while a significant improvement in handgrip strength 24 hours after intense resistance exercise was observed in male adults (36).…”
Section: Discussionsupporting
confidence: 79%
“…Only two previous studies have investigated the effects of a polyphenol-rich intervention on handgrip strength, both of which were performed in male adults (35,36). Supplementation with grape juice in male volleyball athletes did not result in improved handgrip strength (35), while a significant improvement in handgrip strength 24 hours after intense resistance exercise was observed in male adults (36). Similar to our study, several polyphenol-rich intervention studies using different isometric strength tests have observed improvements in recreationally active males and older subjects (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…This study used a double-blind crossover design in which participants completed two trials separated by a 2-wk washout period in line with previous literature (10,15,21,22). The study received ethical approval from the Sport and Health Sciences ethics committee at the University of Exeter and Human Research Ethics committee at the University of Queensland, and all testing conformed to the guidance set out by the Declaration of Helsinki (see additional information for details).…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies have indicated that polyphenol intake is correlated with reduced oxidative stress and improves muscle function following intense resistance exercise. [43][44][45] Therefore, polyphenols play an important role in the improvement of physical performance. Antioxidant activity is crucial in reflecting the biological activity of MLEE.…”
Section: Discussionmentioning
confidence: 99%